Incremental clustering of dynamic data streams using connectivity based representative points - Luhr, Sebastian; Lazarescu, Mihai (Elsevier Science Publishers B. V. Amsterdam, 2009)
We present an incremental graph-based clustering algorithm whose design was motivated by a need to extract and retain meaningful information from data streams produced by applications such as large scale surveillance, network packet inspection and financial transaction monitoring. To this end, the method we propose utilises representative points to both incrementally cluster new data and to selectively retain important cluster information within a knowledge repository. The repository can then be subsequently used to assist in the processing of new data, the archival of critical features for off-line analysis, and in the identification of recurrent patterns.